Pemanfaatan data penjualan sebagai dasar penetapan harga pada Lamongan Mart di Diskoperindag - Ana Fitriyatul Bilgies; Fidia Tasya Vira Ardela; Devi Nofita Sari; Devi Ayu Tristantiya (Penamas: Journal of Community Service, 2026)
The use of sales data as a basis for pricing is a strategic step to increase consumer interest in purchasing MSME products at Lamongan Mart, which the Lamongan Regency Cooperatives, Industry and Trade Office manage. This program aims to improve showroom managers’ understanding and skills in processing sales data to support price determination in line with market conditions and consumer purchasing power. The training method includes providing materials, case studies, sales data analysis, and evaluation through pre-tests and post-tests. The results of the activity showed a 33.5% increase in participants’ understanding of the ability to read consumer demand trends, identify products with high and low sales levels, and establish more competitive pricing strategies. The use of sales data also helps managers make more accurate decisions to support increased sales of MSME products. This activity is expected to strengthen Lamongan Mart’s role as a modern, responsive, and sustainable marketing platform for superior regional products, supporting local economic empowerment.